A History of Italian Wine - Vaquero Piñeiro, Manuel. author. aut Link
XI, 241 p. 21 illus., 14 illus. in color.
Keywords: This book analyzes the evolution of Italian viticulture and winemaking from the 1860s to the new Millennium. During this period the Italian wine sector experienced a profound modernization, renovating itself and adapting its products to international trends, progressively building the current excellent reputation of Italian wine in the world market. Using unpublished sources and a vast bibliography, authors highlight the main factors favoring this evolution: public institutional support to viticulture; the birth and the growth of Italian wine entrepreneurship; the improvement in quality of the winemaking processes; the increasing relevance of viticulture and winemaking in Italian agricultural production and export; and the emergence of wine as a cultural product.